Polycladida Acotylea from Patagonia. Redescription of Crassiplana albatrossi (Pseudostylochidae), lectotype designation and first record of Notocomplana palta (Notoplanidae) - Brusa, Francisco; Damborenea, Cristina (Zootaxa, 2011)
Crassiplana albatrossi is redescribed on the basis of material collected in Patagonia (Argentina) and type material deposited in the USNM. The specimens have specific characters, showing tentacles; tentacular, brain and marginal eyes; genital pores in the posterior portion; male copulatory system with penis papilla; prostatic vesicle free, with strong muscular walls; internal epithelium of prostatic vesicle glandular and with conspicuous projections; seminal vesicle present; vagina very long and extending anteriorly up to pharynx; Lang’s vesicle absent; genito-intestinal duct present. Known geographic range is increased to include Patagonia (Argentina). Identity of Notocomplana palta is confirmed based on the presence of characters in the original description including: strongly muscular seminal vesicle, long, thin and muscular ejaculatory duct stretching into prostatic vesicle, which has a high and folded epithelium; conical penis papilla. A lectotype is designated from the material studied by Marcus and housed in the SMNH. Known geographic range of Notocomplana palta, known only from the type locality in south Chile, is enlarged to include Patagonia (Argentina), revealing its Magellanic affinities.